Fostering Tolerance Among Indonesian Youth: A Muslim-Christian Perspective - Kristina, Ayu; Muttaqien, Zaenal (AL-ADYAN, 2023)
Several studies have found that Indonesian youths (17-24 years old) are vulnerable to religious radicalism. As a result, fostering tolerance among them has been critical. This article describes how Indonesian youths understand religious tolerance and then offers suggestions to foster the attitude of tolerance among Indonesian youth through Muslim-Christian dialogs. For that purpose, a Focus Group Discussion (FGD) was held with ten Indonesian youths (five Muslims and five Christians), which discussed open questions about the issue of tolerance. The discussion's outcomes were examined using a theoretical framework of religious tolerance and inter-religious dialogue. So practical suggestions are obtained for fostering tolerance among Indonesian youth. Such as theological understanding that leads to tolerance and pluralism.